The influence of supply chain practice on supply chain performance in South Africa - Hove, Progress (My University, 2015)
The effective implementation of intra-firm and inter-firm supply chain practices and processes such as supply chain e-collaboration and sharing of important information among supply chain partners, is commonly associated with the creation of supply chain competitiveness and enhanced performance. However, little attention has, thus far, been given to the empirical investigation of the influence of the successful implementation of intra-firm supply chain practice on supply chain e-collaboration, strategic information sharing, supply chain competence and supply chain performance in South Africa. The principal objective of this study was to fill this void by investigating the influence of intra-firm supply chain practice on supply chain e-collaboration among supply chain partners in South Africa. Secondly, the study sought to determine the influence of supply chain e-collaboration on strategic information and supply chain competence among supply chain partners in South Africa. It also aimed to examine the influence of strategic information sharing on supply chain competence and ultimately on the supply chain performance of supply chain partners in South Africa. Lastly, the study sought to ascertain the influence of supply chain competence on supply chain performance of supply chain partners in South Africa. A positivist approach that allowed a quantitative research method in data collection was used in this study. Data from a sample of 280 collaborating firm owners/managers from all the industries of South Africa’s nine provinces was used for the final data analysis of this research. A principal component analysis was performed for factor reduction and dimensional groupings using SPSS 21 software. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were performed for model fit assessments and hypotheses tests respectively, using the Analysis of Moments of Structure (AMOS 21) software. Multiple Regression analysis was performed using SPSS 21 software, and was used for comparison and support of the weak and unsupported SEM hypotheses tests. The principal finding of this study reveals that intra-firm supply chain practice has a strong positive and significant influence on supply chain e-collaboration among supply chain partners in South Africa. In addition, the results showed that supply chain e-collaboration can strongly and significantly enhance the sharing of strategic information among supply chain partners in South Africa. The findings further revealed that supply chain e-collaboration has an ability to create a supply chain competence among supply chain partners in South Africa. The study’s empirical findings also indicate that strategic information sharing has a weak positive and significant indirect influence on supply chain competence and supply chain performance. Lastly, the SEM findings showed that supply chain competence has a weak negative and insignificant influence on supply chain performance. However, the multiple regression analysis showed a weak negative and significant influence of supply chain competence on the supply chain performance of supply chain partners in South Africa. The conclusions and implications of the empirical research findings are provided and recommendations are suggested. The study suggests a new supply chain management conceptual model for research. It also proposes a new supply chain management implementation framework to help guide firms to formulate strategies for improving supply chain performance. The study recommended that the collaborating firm owners/managers consider: training and education for all employees on the importance of supply chain practices and processes such as supply chain e-collaboration and strategic information sharing. Furthermore, it is recommended that collaborating firm owner/managers should consider adopting advanced technologies and information sharing structures to improve their supply chain performance. The collaborating firm owner/managers were also encouraged to align their incentives with the supply chain roles and activities assigned to the supply chain partners. Policy makers were encouraged to make e-business financing arrangements for supply chain collaborating firms; promote synergies between collaborating small and mediums firms and large technology vendors; and ensure affordability of supply chain e-collaboration technologies. The study attempted to address the intra-firm supply chain practice deficiencies on the side of both the supply chain e-collaborating firms and the government.
D. Tech. (Business, Logistics, Faculty of Management Sciences) Vaal University of Technology
Keywords: Supply chain practices; Intra-firm supply chain practice; Supply chain e-collaboration; E-business financing arrangements; Confirmatory Factor Analysis; 658.5; Physical distribution of goods; Business logistics